2020
DOI: 10.5937/ejae17-23638
|View full text |Cite
|
Sign up to set email alerts
|

Have export compositions influenced economic growth of the European Union countries in Central and Eastern Europe?

Abstract: This study analyzes export composition effects on economic growth in the European Union (EU) countries of Central and Eastern Europe (CEE) during 1999-2016. The results confirm that the fuel and food exports have boosted growth after EU accession. As expected, agricultural exports have no effect on growth. Due to the different comparative advantages, the CEE countries have still relied on some raw material exports while developing manufactured exports. The results also indicate that the transportation equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…As the cooperation between China and the CEECs deepens, bilateral trade also increases. Since the introduction of the BRI in 2013, trade between China and CEECs has exhibited continuous growth (Tang 2020). While the growth rate experienced a temporary decline due to the impact of the European refugee wave in 2015, it resumed an upward trend in 2016 and 2017.…”
Section: Trade Characteristics Of China and Ceecsmentioning
confidence: 99%
“…As the cooperation between China and the CEECs deepens, bilateral trade also increases. Since the introduction of the BRI in 2013, trade between China and CEECs has exhibited continuous growth (Tang 2020). While the growth rate experienced a temporary decline due to the impact of the European refugee wave in 2015, it resumed an upward trend in 2016 and 2017.…”
Section: Trade Characteristics Of China and Ceecsmentioning
confidence: 99%
“…Their research showed that there is a stable long-term cointegration relationship between openness to trade and the quality of economic growth. Tang (2020) investigated the combined effects of export structure and economic growth in European Union member countries from Central and Eastern Europe. The research showed that the export of agricultural products does not contribute to economic growth, while transport equipment, textiles, steel and chemical products accelerate the economic growth of the observed countries.…”
Section: Introductionmentioning
confidence: 99%